Chances and Challenges of Mobile Health in Public Health Dentistry - Athira Purushothaman; Rekha P Shenoy; Imran Pasha Mohammad; Junaid; Supriya Amanna (Journal of Clinical and Diagnostic Research, 2023)
The future of healthcare delivery keeps evolving and mobile phone technology may have a huge role to play. Mobile health (mHealth) is a facet of Electronic Health (eHealth) that involves the use of mobile phones and other wireless devices in medical practice. The effectiveness of mHealth has been proven in different studies as well as in different aspects of medicine and dentistry. Text messaging has made significant progress in delivering health education for maintaining oral hygiene, especially for orthodontic patients as well as tobacco cessation counseling. Mobile phone applications incorporate various features like gaming, audio, and video messages to engage smokers in several behavioural change strategies. Mobile health technology has made an immense contribution to contact tracing, screening, and tele-consultation during the Novel Coronavirus Disease-19 (COVID-19) pandaemic. Given that mHealth is a low cost, easily accessible, and widely available means of communication, it has the potential to play a significant role in public health dentistry.